Pengaruh Ketinggian Beban Jatuh dan Kekentalan Oli Suspensi Depan Terhadap Getaran Shock Absorber Sepeda Listrik - Naufal Yunas Oktavian; Purwoko Purwoko (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
One important aspect in choosing a vehicle is comfort, where the suspension plays a significant role. The main suspension component, namely the Shock Absorber, has a crucial role in minimizing vibrations and optimizing driving comfort. The function of the Shock Absorber depends on the viscosity value of the damper, which must support the effectiveness of the suspension. A quantitative experimental type approach was used by taking data using a Vibrator meter. The test is carried out by dropping a load on a load test tool with predetermined variables with the aim of obtaining vibration values ​​on the Shock Absorber. This type of synthetic oil with a viscosity of 77.22 mm²/s, which is used as a filler for the front shock absorber on e-bomber electric bicycles, has the lowest viscosity among other types of oil, resulting in the highest vibration speed. The type of mineral oil with a viscosity of 79.35 mm²/s, which is used as a filler for the front shock absorber on e-bomber electric bicycles, has the highest viscosity among other types of oil, resulting in the lowest vibration speed. This type of semi-synthetic oil with a viscosity of 78.31 mm²/s, has a viscosity that is between synthetic and mineral oil types, resulting in a higher vibration speed compared to synthetic oil types but lower than mineral oil types.